Stitching automático de imágenes panorámicas con drones para la digitalización de zonas rurales aisladas (2022)
In the present project a Stitching algorithm is developed and simulated, which has the function of joining images captured by the simulation of a drone in Matlab and Simulink in a completely automatic way